Legal Empirical Public Health Analysis of Smoke Free Regulation Revision in Kulon Progo - Sapardiyono Sapardiyono (Universitas Muhammadiyah Tangerang, 2025)
This article aims to analyze the discourse surrounding the revision of the Local Regulation on Smoke-Free Zones (KTR) in Kulon Progo Regency from a legal-empirical perspective, focusing on aspects of public health protection and the consistency of local policies. This study employs a legal-empirical method using a regulatory approach and a sociological approach. Data were collected through document analysis and policy analysis, supported by the evolving social dynamics within the community. The results indicate that the revision of the KTR Regional Regulation has the potential to weaken public health protection and reduce the consistency of the local government in implementing health-based policies. On the other hand, there are socio-economic pressures driving regulatory flexibility. Therefore, a policy approach oriented toward the long-term interests of the community is needed, while maintaining a balance between individual rights and collective rights to a healthy environment.